Translation Theory: A Historical-Thematic Account - EL KHATIBI, MOURAD (International Journal of Language and Literary Studies, 2024)
The main function of Translation Studies is to study issues of translation production and propose solutions for translation problems. Today, Translation Studies is an academic discipline that is gaining more recognition in the academic community. More than that many scholars of different backgrounds and fields of study like literature, history, anthropology, semiotics, and philosophy have been attracted by translation studies. This article is divided into three sections. The first section presents a brief history of Translation Studies. The second section discusses definitions and meanings of the word ’translation’. The third section analyses different theories of translation.